2015
DOI: 10.1177/0309324715595141
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition-based calibration/validation metrics for use with full-field measurement situations

Abstract: Calibration and validation metrics that involve decomposition of simulation and test data have been developed for potential use in the quantification of margin and uncertainty. The uniqueness of these validation metrics allows for nearly fullfield, simulation and test data over a wide range of spatial realizations (three-dimensional responses over multiple input conditions) and temporal (time or frequency) information, as needed. Currently, no other calibration/validation metrics have been developed that span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The result of the modal assurance criterion is a value between 0 and 1 indicating the quality of agreement. This normalization makes it difficult to define an acceptance criterion as the criterion output cannot be related to the measurement uncertainty of the experiment [ 5 ]. Others have explored using singular value decomposition to compare mode shapes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the modal assurance criterion is a value between 0 and 1 indicating the quality of agreement. This normalization makes it difficult to define an acceptance criterion as the criterion output cannot be related to the measurement uncertainty of the experiment [ 5 ]. Others have explored using singular value decomposition to compare mode shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Others have explored using singular value decomposition to compare mode shapes. These approaches reduce the dimensionality of the data by projecting it onto an orthogonal set of kernels resulting in a feature vector with the same units as the originally measured or simulated data-field [ 5 ]. This feature vector is therefore more readily related to the measurement uncertainty of the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency response of each of these 20 descriptors was then computed to produce the so-called shape descriptor frequency response function (SD-FRF), and the first 11 mode shapes were constructed from the 20 shape descriptors. Subsequently, Allemang et al 25,26 explored the use of principal component analysis (PCA), based on singular value decomposition (SVD), to perform similar transformations on their data. They concluded that the results obtained from SVD-PCA and orthogonal decomposition techniques were comparable, but the former was more straightforward to implement.…”
Section: Introductionmentioning
confidence: 99%
“…The use of decomposition methods to reduce the dimensionality of the resultant data and enable more straightforward comparisons has also been established. 13,[25][26][27] While, recently, Berke et al 28 have shown the correlation between modal shapes for simple rectangular plates and the kernels of the Chebyshev polynomials used in orthogonal decomposition. Hence, orthogonal decomposition based on Chebyshev polynomials was chosen for use in this study to reduce the dimensionality of the out-of-plane displacement fields measured using stereoscopic DIC.…”
Section: Introductionmentioning
confidence: 99%
“…An example for the use of decomposition methods as an essential part of full-field validation process is described by engineers of the aerospace field. 3 They conclude that the decomposition methods successfully quantify margin and uncertainty in their approach to validation metrics.…”
mentioning
confidence: 97%